THE EFFECT OF USING NOTING INTERACTING SUMMARIZING AND PRIORITIZING STRATEGY ON STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION - Maruh Sianturi and Berlin Sibarani (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2013)
This study was aimed at finding out the effect of using Noting, Interacting, Summarizing, and Prioritizing Strategy on Students’ Achievement in Reading Comprehension. This study was designed with the experimental design. The population of this study was the first year students at academic 2013/2012 of SMA swasta YP St. Paulus Martubung, Medan. There were fourty students taken as the sample of the research. The sample was divided into two groups: the first group (20 students) as the experimental group and the second group (20 students) as the control group. The experimental group was taught by Using Noting, Interacting, Summarizing, and Prioritizing Strategy, while the control group was taught by using conventional method. The instrument for collecting the data was multiple choices which consisted of 40 items. To obtain the reliability of the test, the researcher used Kuder -Richardson (KR-21) formula. The calculation showed that the reliability of the test was 0.75. The data were calculated by using t-test formula. The result of the analysis shows that t-observed (4.98) was higher than t-table (2.025) at the level of significance (α) 0.05 and the degree of freedom (df) 38. Therefore, the null hypothesis (H0) was rejected and alternative hypothesis (Ha) was accepted. It meant that teaching reading comprehension by using Noting, Interacting, Summarizing, and Prioritizing Strategy significantly affects reading comprehension.